Sestrin2 Suppresses Classically Activated Macrophages-Mediated Inflammatory Response in Myocardial Infarction through Inhibition of mTORC1 Signaling - Yang, Keping; Xu, Chenhong; Zhang, Yunfeng; He, Shaolin; Li, Dazhu (Frontiers in Immunology, 2017)
Myocardial infarction triggers an intense inflammatory response that is essential for dead tissue clearance but also detrimental to cardiac repair. Macrophages are active and critical players in the inflammatory response after myocardial infarction. Understanding the molecular mechanisms by which macrophage-mediated inflammatory response is regulated is important for designing new therapeutic interventions for myocardial infarction. In current study, we examined the role of Sestrin2, which is a stress-inducible protein that regulate metabolic homeostasis, in the regulation of inflammatory response of cardiac macrophages after myocardial infarction. We found that cardiac macrophages up-regulated Sestrin2 expression in a mouse myocardial infarction model. Using a lentiviral transduction system to overexpress Sestrin2 in polarized M1 and M2 macrophages, we revealed that Sestrin2 predominantly functioned on M1 rather than M2 macrophages. Sestrin2 overexpression suppressed inflammatory response of M1 macrophages both in vitro and in vivo. Furthermore, in the mouse myocardial infarction model with selective depletion of endogenous macrophages and adoptive transfer of exogenous Sestrin2-overexpressing macrophages, the anti-inflammatory and repair-promoting effect of Sestrin2-overexpressing macrophages was demonstrated. Furthermore, Sestrin2 significantly inhibited mTORC1 signaling in M1 macrophages. Taken together, our study indicates the importance of Sestrin2 for suppression of M1 macrophage-mediated cardiac inflammation after myocardial infarction.